Yes, we’re open! - Babette Knauer; Josca Westerhof (o-bib. Das offene Bibliotheksjournal, 2024)
Academic libraries are pivotal for advancing Open Science initiatives, as they serve as hubs for knowledge dissemination. However, strategies for communication about Open Science support that address the academic community are often shaped by policy objectives rather than by the needs of the target audience. This approach fails to resonate with researchers, the primary stakeholders in the Open Science ecosystem, and does not reflect the practical realities of conducting research. Therefore, the University of Groningen Library developed a dialogue-based communication approach. This strategy involves gathering input, building consensus, identifying multipliers, sharing best practices and letting researchers speak for themselves. In this article, we elaborate on this approach, highlighting critical tools: our Open Science Ambassadors, collaboration with grassroots initiatives, and interactive media strategies. These mechanisms facilitate dialogue with the academic community, enhancing visibility of our Open Science services.